2008
DOI: 10.1016/j.leukres.2007.05.008
|View full text |Cite
|
Sign up to set email alerts
|

PU.1 is dispensable to block erythroid differentiation in Friend erythroleukemia cells

Abstract: Friend murine erythroleukemia cell lines derive from erythroblasts transformed with the Friend complex where the spleen-focus forming virus integrated in the vicinity of the Sfpi-1 locus. Erythroleukemia cells do not differentiate and grow indefinitely in the absence of erythropoietin. Activation of the transcription factor PU.1, encoded by the Sfpi-1 gene, is thought to be responsible for the transformed phenotype. These cells can overcome the blockage and reinitiate their differentiation program when exposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
24
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 46 publications
7
24
0
Order By: Relevance
“…We found that the pattern of the major cell cycle phases, G1 vs S vs G2/M, was similar between MEL-R cells and undifferentiated MEL progenitors (MEL-0 h). By contrast, differentiated MEL cells (MEL-96 h) accumulated at G1, a phenomenon that has been previously observed during MEL cell differentiation (Kiyokawa et al, 1993; Vanegas et al, 2003; Fernández-Nestosa et al, 2008). Nevertheless, we observed that in terms of DNA content, MEL-R cells acquired a tetraploid phenotype as revealed by the shift in DNA content to the right (Fig.…”
Section: Resultssupporting
confidence: 50%
See 4 more Smart Citations
“…We found that the pattern of the major cell cycle phases, G1 vs S vs G2/M, was similar between MEL-R cells and undifferentiated MEL progenitors (MEL-0 h). By contrast, differentiated MEL cells (MEL-96 h) accumulated at G1, a phenomenon that has been previously observed during MEL cell differentiation (Kiyokawa et al, 1993; Vanegas et al, 2003; Fernández-Nestosa et al, 2008). Nevertheless, we observed that in terms of DNA content, MEL-R cells acquired a tetraploid phenotype as revealed by the shift in DNA content to the right (Fig.…”
Section: Resultssupporting
confidence: 50%
“…1B. Sfpi1/PU.1 was one of the selected genes that, as we demonstrated previously (Fernández-Nestosa et al, 2008), is not expressed in the resistant cell line and served in this case as a positive control for the RNA-seq efficiency. We observed that the majority of the differentially expressed genes are up-regulated in MEL compare to MEL-R cells (Fig.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations